Quantum Systems for Enhanced High Energy Particle Physics Detectors - Doser, M.; Auffray, E.; Brunbauer, F.M.; Frank, I.; Hillemanns, H.; Orlandini, G.; Kornakov, G. (Frontiers in Physics, 2022)
Developments in quantum technologies in the last decades have led to a wide range of applications, but have also resulted in numerous novel approaches to explore the low energy particle physics parameter space. The potential for applications of quantum technologies to high energy particle physics endeavors has however not yet been investigated to the same extent. In this paper, we propose a number of areas where specific approaches built on quantum systems such as low-dimensional systems (quantum dots, 2D atomic layers) or manipulations of ensembles of quantum systems (single atom or polyatomic systems in detectors or on detector surfaces) might lead to improved high energy particle physics detectors, specifically in the areas of calorimetry, tracking or timing.